Cardiovascular and cardiac therapeutic devices - Franz, Thomas (Studies in Mechanobiology, Tissue Engineering and Biomaterials, 2014)
This volume focuses on latest research in therapeutic devices for cardiovascular, i.e. vascular and valvular, and cardiac diseases. Aspects of vascular therapies covered relate to stent grafts for aortic aneurysms, endovascular stents for percutaneous arterial interventions, and small- to medium-diameter tissue engineered vascular grafts - one of the greatest persisting challenges in cardiovascular therapies. Contributions on valvular therapies focus on prosthetic heart valves with flexible polymeric leaflets and patient-specific simulation for open-heart and percutaneous implantation of aortic biological heart valves including the challenges posed on the prosthesis design. The section on cardiac diseases provides contributions on advances in therapies for myocardial infarction and infarct-induced heart failure, and in vivo biomechanics of implantable cardiac pacemakers.